The Influence of Leadership, Rewards, And Development on Engagement Mediated by Organizational Culture - Syarini, Rina; Dewi Susita; Umi Widyastuti (International Journal of Computational and Experimental Science and Engineering, 2025)
This study investigates the influence of empowering leadership, reward systems, and employee development on employee engagement, with organizational culture as a mediating variable. The research was conducted in the Indonesian Ministry of Home Affairs using a quantitative explanatory approach with survey methods. A total of 376 civil servants were selected through purposive sampling. Data were collected using a structured questionnaire measured on a 5-point Likert scale and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that all three independent variables empowering leadership, reward systems, and employee development significantly and positively affect employee engagement. Among them, empowering leadership had the strongest direct influence, followed by employee development. Reward systems showed a relatively weaker direct effect but became significant when mediated by organizational culture. The mediating role of organizational culture was proven to be partial for leadership and development, and full for rewards, highlighting the critical function of shared values and norms in enhancing engagement. These findings reinforce both the Job Demands-Resources (JD-R) model and Social Exchange Theory (SET), emphasizing that employee engagement in the public sector is shaped not only by managerial practices but also by an enabling and cohesive organizational culture. Practical implications point to the importance of integrating leadership empowerment, fair rewards, career growth, and cultural alignment to foster a more engaged and resilient public workforce.